Genomic analysis of a nontoxigenic, invasive Corynebacterium diphtheriae strain from Brazil - Fernando Encinas; Michel A Marin; Juliana N Ramos; Verônica V Vieira; Ana Luiza Mattos-Guaraldi; Ana Carolina P Vicente (Memorias do Instituto Oswaldo Cruz, 2015)
We report the complete genome sequence and analysis of an invasive Corynebacterium diphtheriae strain that caused endocarditis in Rio de Janeiro, Brazil. It was selected for sequencing on the basis of the current relevance of nontoxigenic strains for public health. The genomic information was explored in the context of diversity, plasticity and genetic relatedness with other contemporary strains.